AFRICAN PHILOSOPHY BEYOND EUROCENTRIC CONCEPTS AND CATEGORIES: A CONVERSATIONAL DISCOURSE - Ezeogu, Uchenna Azubuike; Ezugwu, Umezurike John (Nnamdi Azikiwe Journal of Philosophy, 2021)
One of the major challenges faced by African philosophy is the persistent presence of Eurocentric concepts and categories in African philosophy discourse. Western philosophy in its hegemonic nature imposed its methods on African philosophy. Due to this, African philosophy is approached through Western Eurocentric narrative. This is explainable when we consider the 'double bind' argument. Oh yes, one cannot adopt Western philosophical method in addressing African philosophy and expect to arrive at something different from Western philosophy. The persistent presence of Eurocentric concepts and categories in African philosophy has continued to question the authenticity or genuineness of African philosophy. The unanswered question is: How can African philosophy go beyond Eurocentric concepts and categories? In this paper, we argue that African philosophy can achieve this feat under review, through conversational philosophy, which is multicultural and transcultural in nature. In line with this, we conclude that African philosophy should not be tailored to conform or gain Western Eurocentric acceptability; it should rather be designed to be inclusive, interdependence and intercultural, for global expansion of thought.
Keywords: African Philosophy; Eurocentrism; Conversationalism; Epistemic injustice; Concepts and categories